2014
DOI: 10.1186/1477-7827-12-7
|View full text |Cite
|
Sign up to set email alerts
|

The term basal plate of the human placenta as a source of functional extravillous trophoblast cells

Abstract: BackgroundExtravillous trophoblast (EVT) cells are of pivotal importance in human embryo implantation and homeostasis of the maternal fetal interface. Invasion of the endometrium by EVT contributes to placental anchorage, spiral artery remodeling, immunological defense, tolerogenic responses, and several collaborative cross talks involved in establishing and maintaining a successful pregnancy. We report here an improved protocol for the isolation of fully differentiated EVT cells from the basal plate of the hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 46 publications
3
29
0
Order By: Relevance
“…Interestingly, our previous study demonstrated that the extravillous trophoblast cells retained some capacity for migration and invasion, though it was less than in first trimester placentas [37]. These findings reinforce the conclusion that CRIPTO-1, mostly expressed in potentially invasive cells, is associated with this cellular activity.…”
Section: Discussionsupporting
confidence: 71%
“…Interestingly, our previous study demonstrated that the extravillous trophoblast cells retained some capacity for migration and invasion, though it was less than in first trimester placentas [37]. These findings reinforce the conclusion that CRIPTO-1, mostly expressed in potentially invasive cells, is associated with this cellular activity.…”
Section: Discussionsupporting
confidence: 71%
“…Cytotrophoblasts are known to have the potential for transforming to the invasive phenotype [Guilbert et al, 2002;Borbely et al, 2014]. Our research showed that PPTC still exhibited invasiveness, which is consistent with earlier findings [Hohn and Denker, 2002;Borbely et al, 2014;Duzyj et al, 2015].…”
Section: Discussionsupporting
confidence: 82%
“…Our research showed that PPTC still exhibited invasiveness, which is consistent with earlier findings [Hohn and Denker, 2002;Borbely et al, 2014;Duzyj et al, 2015]. However, of note, EVT also express cytokeratin 7, and it is possible that purified cytotrophoblasts contaminated with EVT exhibit invasiveness once incubated in Matrigel-coated Transwell inserts.…”
Section: Discussionsupporting
confidence: 82%
“…This cluster of cells is unique in its expression of nonclassical human leukocyte antigen HLA-G and integrin 5 alpha ITGA5-both considered markers of extravillous trophoblast, KRT7 (Telugu et al 2013;Borbely et al 2014) and ADAM12 (Biadasiewicz et al 2014). Further EVT-specific genes and other highly expressed genes are listed in Tables 1 and 2 and discussed in the Supplemental Material.…”
Section: Extravillous Trophoblast (Evt; Cluster 5)mentioning
confidence: 99%